The Anglophone Question in Cameroon: Historical Context and Evolution from “Everyday” Resistance to Armed Conflict, 1961-2017 - e Reymond Njingti Budi, Confidence Chia Ngam (Africana Studia, 2021)
Since 2017, English-speaking regions of Cameroon have witnessed armed conflict in its towns and villages with far-reaching repercussions. This is perhaps one of the worst endogenous armed conflicts in Cameroon since independence in 1960 and reunification in 1961. What is even more engrossing to the mind has been the question as to how corporatist movements initiated by Cameroon Anglophone common law lawyers and teachers soon vitiated into armed confrontation on a scale that can only be compared to anti-colonial movements in French Cameroon from the 1940s to the 1960s. From this basic premise, this paper contends that the armed conflict witnessed in the Anglophone regions since 2017 did not emerge from a vacuum. It has been in gestation in the form of “everyday” resistance since at least the 1970s. The armed conflict has been a concomitant feature of historical milestones marked by accumulated grievances and frustrations, gelled by the growth of ‘Ambazonism’, propagated as the twin phenomena of liberalism and nationalism through the social media and sponsored and steered by an ensemble of Cameroonian Diaspora enjoying immunity afforded by geography and distance. The paper wields an avalanche of diverse sources ranging from archival, published and oral material to sustain its thesis. Keywords: Anglophone Cameroon, ‘Everyday’ Resistance, Armed Conflict and Ambazonism.